CSUCI Enrollment Management: Our Way Forward - Richard Yao:::President::: (2023)
Our Strategic Enrollment Management Plan focuses on a number of immediate strategies to improve new student recruitment and yield through the targeted use of data, while concurrently focusing on the intermediate and longer-term planning necessary for the strategic success of CSUCI.